Unions in Digital Labour Studies: A Review of Information Society and Marxist Autonomist Approaches - Tai Neilson (tripleC: Communication, Capitalism & Critique)
A developing research agenda in digital labour studies draws on aspects of information society theory and Marxist autonomism to understand examples of unionisation in digital workplaces and among digital labourers. In this article, I trace core concepts of information society theory and autonomism to demonstrate how unions have been framed by prominent figures in the field. I argue that both approaches tend to relegate unions to industrial capitalism and its historically-specific set of class relations. Information society theorists argue that capitalist class conflict has been transcended, perceiving unions as an obstacle to flexibility and entrepreneurship. Autonomists maintain a focus on class conflict, yet, based on their analysis of contemporary class composition, tend to prioritise other forms of organisation over unions. Digital labour studies research has developed, in part, as a critique of information society theory and draws on aspects of autonomism, including the concepts of precarity and immaterial labour. Authors studying empirical examples of unionisation among digital labourers identify different challenges and opportunities for unionisation among digital labours, and demonstrate the utility of unions for improving the conditions of digital labourers and promoting new working-class subjectivities.